3D micro pattern generation by electrochemical micromachining (EMM) process. (2nd March 2015) - Debnath, S.; Mahata, S.; Bandyopadhyay, K.; Bhattacharyya, B.
Electrochemical micromachining (EMM) is an anodic dissolution process that removes material electrochemically and exhibits tremendous potential due to its outstanding advantages it offers in fabricating complex micro features for machine micro parts to be used widely in various high end and sophisticated areas. But, in spite of this, generating 3D micro structures, in micrometer levels is still very complicated. Therefore, theoretical analysis and development of mathematical model for 3D micro pattern generation by EMM has been carried out. The present work is also directed towards machining of 3D micro pattern of an air lubricated bearing with EMM where attempts has been made to investigate the effect of influencing process parameters on depth and roughness values of the generated micro patterns.